3D virtual intravascular endoscopy visualization of coronary artery plaques: Virtual intravascular endoscopy of coronary plaques - Sun, Zhonghua; Chaichana, T.; Dimpudus, F.; Adipranoto, J.; Nugroho, J. (2009)
The purpose of the study is to investigate the potential diagnostic value of 3D virtual intravascular endoscopy in the visualization of coronary artery plaques in patients with suspected coronary artery disease. Ten patients suspected of coronary artery disease undergoing 64-slice computed tomography scans were included in the study. Four main coronary artery branches including right coronary artery, left main stem, left anterior descending and left circumflex were assessed using virtual intravascular endoscopy with emphasis on the intraluminal appearance of coronary plaques (calcified and noncalcified plaques). Position of the plaques and degree of vessel stenosis was compared with 2D axial images in each patient. Coronary artery disease with >50% stenosis was found in 6 patients involving 7 left anterior descending and 3 right coronary artery branches. Left anterior descending branch was commonly affected with extensive calcification, while more than half of the right coronary arteries were involved with noncalcified plaques. Our results showed that virtual intravascular endoscopy provides unique information of the coronary plaques by demonstrating the intraluminal configuration of coronary plaques, position of the plaques in relation to the artery branches. Both calcified and noncalcified plaques can be identified on virtual endoscopy images. Further studies are needed to clarify the role of virtual intravascular endoscopy in the quantification of plaque volume, stratification of patients suffering from coronary artery disease and patients management. ©2009 IEEE.